2021
DOI: 10.1007/s40005-021-00544-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of ZnO/Berberine complex contract COVID-19 and respiratory co-bacterial infection in addition to elimination of hydroxychloroquine toxicity

Abstract: Purpose A novel coronavirus (COVID-19) that has not been previously identified in humans and has no specific treatment has recently spread. Treatment trials using antiviral and immune-modulating drugs such as hydroxychloroquine (HCQ) were used to control this viral outbreak however several side effects have emerged. Berberine (BER) is an alkaloid that has been reported to reveal some pharmacological properties including antioxidant and antimicrobial activities. Additionally, Zinc oxide nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…It should be noted the aforementioned respiratory viruses, even despite using different cellular pathways, share the existence of the ACE2 protein at the beginning of the digestive system and upper respiratory tract (discussed earlier) [215] , which represents an excellent motivation for the proposed therapy with Zn NPs. The results of nano Zn compounds in various models studies for antiviral action against the emerging respiratory virus are summed up in Table 4 [136] , [141] , [158] , [212] , [213] , [216] , [217] , [218] .…”
Section: Zn As An Essential Element In Emerging Virus Mediated-respir...mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted the aforementioned respiratory viruses, even despite using different cellular pathways, share the existence of the ACE2 protein at the beginning of the digestive system and upper respiratory tract (discussed earlier) [215] , which represents an excellent motivation for the proposed therapy with Zn NPs. The results of nano Zn compounds in various models studies for antiviral action against the emerging respiratory virus are summed up in Table 4 [136] , [141] , [158] , [212] , [213] , [216] , [217] , [218] .…”
Section: Zn As An Essential Element In Emerging Virus Mediated-respir...mentioning
confidence: 99%
“… [213] ZnSO 4 (zinc II) NPs Influenza A Virus (H9N2) in embryonated Specific-Pathogen-Free hen's eggs ZnSO 4 (1.5 mg/mL) and Ag NPs comparable antiviral action with epigallocatechin gallate EGCG (50 μM) against the H5N1 avian flu virus Potentiated antiviral activity of EGCG by co-administering it with zinc II and AgNPs [212] ZnO NPs BALB/c mice injected with M. pneumoniae Reduced total protein, inflammatory cells , inflammatory cytokines (IL-1, IL-6, IL-8, TNF-a and TGF). Potential effects against upper and lower respiratory tract infections [216] ZnO/ Berberine (BER) complex VeroE6 toxicity, anti-COVID-19 activity ZnO/BER complex inhibits spike protein binding with angiotensin-converting enzyme II (ACE II), PL pro activity, spike protein and E protein levels, and expression of both E-gene and RNA dependent RNA polymerase (RdRp) It acts as an anti-COVID-19 and could be used to treat a second bacterial infection [217] Au-NP/Ag-NP/ZnO-NP and ClO2 nanocomposite (TPNT1) SARS-CoV-2 strains in vitro cell-based assay Block viral entry by inhibiting the binding of spike proteins to ACE2 receptor and to interfere with the syncytium formation Effective concentration within the range to be used as food additives provide prophylactic effects against both SARS-CoV-2 [273] Au-NP/Ag-NP/ZnO-NP and ClO2 nanocomposite (TPNT1) (H1N1) and avian influenza A virus (H5N1) cell-based assays Reduced the cytopathic effects induced by human H1N1 and avian H5N1 influenza viruses, including oseltamivir-resistant virus isolates Inhibit or prevent viral infectionand opportunistic infections [273] ZnO NPs COVID-19 targets include the ACE2 receptor, COVID-19 RNA-dependent RNA polymerase in humans in lung fibroblast cells and in silico molecular docking The binding of ZnO NPs with the three tested COVID-19 targets via hydrogen bond formation was detected. Infer further biological and therapeutic studies [158] EGCG-AgNPs/ZnSO 4 Influenza A Virus (H9N2) in embryonated Specific-Pathogen-Free hen's eggs Co-treatment with ZnSO 4 (1.3 mg/m...…”
Section: Zn As An Essential Element In Emerging Virus Mediated-respir...mentioning
confidence: 99%
“…However, Zn could be employed to improve the performance of other antiviral agents. Ghareeb et al [ 217 ] combined ZnO NPs with berberin (BER), an isoquinoline alkaloid with antimicrobial activity and antiviral properties [ 218 ], by absorption of cationic BER molecules on the surface of negatively charged ZnO NPs. In silico analyses demonstrated that the ZnO BER complex binds to PLpro (through O with O-atom in Asp77 and Glu78), to spike protein (through its O atom with O-atom of Ile666 and Pro862) and to the spike protein RBD (through hydrophobic interactions).…”
Section: Nanomaterials For Covid-19 Prevention and Treatmentmentioning
confidence: 99%
“…For biosensing, a few stages depend on gold, selenium, iron, Graphene, and zinc [46][47][48][49][50][51][52] . In any case, only the elements which have been read up for biosensor stages is zinc because of its superb optical and electronic functionalities, with the extra benefit of being modest and plentiful in features.…”
Section: Implementation Of Zinc Based Nanomaterials In Fighting Again...mentioning
confidence: 99%